O03.5 Recent Increases in Gonorrhoea in Europe. (13th July 2013) - Spiteri, G; Haar, K; Sfetcu, O; Laar, M van de
Abstract : Background: Recent reports have described increasing trends of gonorrhoea among men who have sex with men (MSM) in the United Kingdom and women in Sweden. European Union (EU/EEA) surveillance data has also shown increasing rates of gonorrhoea since 2008. We analysed surveillance data to identify the contributions of key populations to this increase. Methods: Surveillance of gonorrhoea in the EU/EEA is co-ordinated by the European Centre for Disease Prevention and Control (ECDC). Data reported to ECDC in 2008 and 2011 were compared, focusing on countries with an increasing number of gonorrhoea cases, to analyse changes among key populations. Results: In 2011, 39 179 cases of gonorrhoea were reported from 28 EU/EEA countries. Of these countries, 21 reported a median increase in the number of reported cases of 31% (interquartile range: 22–79%). Among countries reporting increasing cases, 15–24 year olds accounted for 43% of reports in 2011; males accounted for 72%; MSM for 40%. Among MSM, the largest proportion of cases was reported among 25–34 year olds (42%). Between 2008 and 2011, the number of reported cases increased by 37%. Increases were observed among all age-groups, particularly among 25–34 year olds (61%) and those aged 45+ (78%). Reported cases increased by 51% among males compared to 30% among females. Transmission among MSM increased by 124% since 2008 and, among MSM, the largest increase in reported cases was among those aged 45+ (192%) and 25–34 year olds (173%). Conclusions: Although reported cases of gonorrhoea increased among all age-groups and both genders between 2008 and 2011, the highest increase occurred among MSM above 25 years of age. Increasing trends may be due to increased awareness and testing, and improved reporting; increased transmission, however, is also likely. Prevention messages targeting these groups need to be reinforced.